THEORY CONCEPT OF HILDEGAR E PEPLAU’S NURSING MODEL IN MENTAL NURSING CARE WITH THE RISK OF VIOLENT BEHAVIOR IN THE KUTILANG WARD OF THE PROVINCIAL MENTAL HOSPITAL BENGKULU IN 2025 - Fitri, Riza; Nursanti, Irna (STIKes RSPAD RSPAD Gatot Soebroto, 2025)
Analysis of the interpersonal relationship theory by Hildegard E Peplau explain the basic concepts of the theory that focuses on human, health, nursing and environmental aspects. This theory is also one of the most influential nursing models in psychiatric nursing practice, especially in treating patient at risk of violent behavior. In its application, this theory forms a dynamic and continuous interpersonal relationship between nurses and patients. This interpersonal relationship is divided into four phases of therapeutic relationship between nurses and patients, namely the orientation phase, the identification phase, the exploitation phase and the resolution phase. Here we discuss the concept of Peplau’s theory and its application to psychiatric nursing care in the kutilang ward of the Bengkulu Provincial Mental Hospital for patient with medical diagnosis of schizophrenia who experiences auditory hallucination and is at risk of violent behavior. The application of the theory focuses on therapeutic communication, assessing, triggers of aggression, establishing trusting relationships and developing adaptive coping through. Structured interventions based on the SDKI-SLKI-SIKI. The result of the application show a decrease in improvement in patient’s self-esteem. The theoretical analysis shows that the Peplau model has advantages in building effective interpersonal relationships and increasing patient involvement in the recovery process. However, this theory has limitations in patients with severe psychosis who find it difficult to establish optimal therapeutic contact, and it underemphasizes the biological aspects often needed in the acute phase. Overall, Peplau’s theory has proven relevant and effective as humanistic, relationship-oriented approach to psychiatric nursing.